Prognosis of oral squamous cell carcinoma with perineural invasion: A comparative study of classification types. (19th November 2019) - Park, Jae; Megow, Anna; Swalling, Adam; Hodge, John‐Charles; Foreman, Andrew; Boase, Samuel; Valentine, Rowan; Krishnan, Suren; Ooi, Eng H.
Abstract: Objective: To investigate the histological location and extent of perineural invasion (PNI) as prognostic factors. Design: Retrospective review of medical records and histological analysis of 116 patients with oral squamous cell carcinoma (OSCC). Setting: Two major public tertiary hospitals treating head and neck cancer, Royal Adelaide Hospital and Flinders Medical Centre, in South Australia. Participants: Patients diagnosed with OSCC who underwent primary surgical treatment with curative intent at these two centres from January 1, 2005 through December 31, 2015. Main Outcome Measures: The primary end points were disease‐free survival (DFS) and disease‐specific survival (DSS). Results: The presence of PNI as a binary factor alone did not significantly influence the clinical outcomes. Extratumoural (ET) PNI as measured from the tumour edge was associated with worse DFS on multivariate analyses. Multifocal PNI was associated with worse DFS and DSS. DFS in multifocal PNI was worse irrespective of whether adjuvant therapy was administered. Conclusions: The presence of multifocal and ET PNI in OSCC is associated with poor clinical outcomes. Patients with multifocal PNI were associated with worse DFS even with adjuvant therapy.